Stability and adaptability of lettuce cultivars on different substrates - Silva, José Luís Tavares; Cavalcante, Marcelo; Barros, José Anderson Soares (Comunicata Scientiae, 2022)
Lettuce is a leafy species cultivated in different regions of the world. During the seedling production process, the choice of the substrate is one of the most important steps. Considering diversity of type and price, it is common to produce alternative substrates using inputs with potential to cause environmental impacts. Sludge is a waste from water treatment plants, which has agricultural potential. This research aimed to estimate the stability and adaptability of five lettuce cultivars under different substrate compositions in the early stages of growth and yield. Two experiments were carried out in 2021: 1) in greenhouse, in which five cultivars (‘Veneranda’, ‘Camila’, ‘Elba’, ‘Vitória Verdinha’, ‘Diva’), three substrates (‘Vida Verde’, Bioplant 434, Bioplant 401) and three sludge doses (0, 20, 40%) were tested on the seedling quality index (SQI); 2) at field level, the yield of seedlings produced in the 1st stage was evaluated. From a double-entry table (matrix M), consisting of five cultivars and nine environments (combination of 3 substrates x 3 sludge doses), deviance analysis, WAASB and ASV stability indexes, biplots of the AMMI method and BLUPs were applied. Significant GE interaction identified cultivars adapted to specific substrates. ‘Camila’ cultivar was stable in terms of SQI and yield; ‘Diva’ was the most unstable, but with specific adaptation to five substrate for SQI and three for yield. The addition of 40% of sludge reduced the SQI; however, it did not influence the yield when associated with ‘Vida Verde’ and Bioplant 434, being indicated for production of lettuce.